Islamic Socio-Economic Hybridity and Market Resilience: Sharia-based Informal Muamalah in Penginyongan-Priangan Borderland - Masngudi Masngudi; Doddy Afandi Firdaus; Rahardi Mahardika; Ahmad Rezy Meidina; Imam Sibawaih (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
Border economies are frequently portrayed as peripheral and fragile, yet many remain commercially vibrant because everyday exchange is organized through informal institutions rather than formal contracting. While the resilience of borderland markets has been examined through social capital and transaction-cost frameworks, the normative role of Islamic muāmalah ethics — particularly amānah (trustworthiness) and ukhuwah (brotherhood) — as an informal regulatory infrastructure sustaining market coordination in Muslim-majority domestic borderlands remains theoretically underspecified and empirically understudied. This study addresses that gap by examining how Penginyongan–Priangan cultural hybridity in the Central Java–West Java border corridor functions as a Sharia-grounded resilience strategy in informal markets and micro and small enterprise networks. Employing a qualitative case study design, empirical materials were generated through in-depth interviews with 15 purposively selected key informants — traders, intermediaries, market governance figures, and community elders — and systematic market observation, analyzed through iterative thematic coding in which Islamic socio-economic variables were integrated as analytical categories alongside sociological mechanisms. The findings establish three conclusions. First, hybridity functions as an informal resilience infrastructure rather than a descriptive identity label: market actors enact it as a practical repertoire that keeps exchange workable during disruption. Second, this infrastructure operates through three interlinked mechanisms — linguistic calibration via code-switching that reduces negotiation frictions; liquid solidarity sustained by multi-channel reputational governance that enables trust and informal enforcement across overlapping communities; and cross-provincial network diversification that supports rapid supplier switching, demand flexibility, and informal credit as social insurance when shocks occur. Third, and constituting the study's primary theoretical contribution, these mechanisms are not merely cultural practices but substantive expressions of Islamic muāmalah ethics: reputational governance enacts amānah as a religious obligation; cross-ethnic solidarity operationalizes ukhuwah as a localized moral economy; and informal credit practices exhibit structural alignment with Qard al-Hasan (interest-free social lending) and Tawāḍu' (mutual consent pricing), demonstrating that Sharia-based informal muāmalah — not formal contracting — constitutes the primary coordinating institution of this borderland economy. This study contributes to Islamic economic governance literature by providing the first empirical specification of how muāmalah ethics function as resilience infrastructure in a Muslim-majority domestic borderland, while extending social capital and transaction-cost theory by demonstrating that enacted cultural competencies compress perceived distance, lower transactional frictions, and expand adaptive options in ways that align with — rather than merely parallel — Islamic normative principles of fair exchange. Policy implications include the recognition of cross-border market integration as an existing Islamic institutional reality and the support of Sharia-compatible cooperative financial mechanisms — particularly Qard al-Hasan lending and Takāful-style mutual guarantee networks — as instruments for amplifying existing resilience capacities in informal border economies